The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1158/1055-9965.epi-16-0185
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Body Fatness, Serum Anti-Müllerian Hormone, and Breast Density in Young Adult Women

Abstract: Background Emerging evidence suggests positive associations between serum antimüllerian hormone (AMH), a marker of ovarian function, and breast cancer risk. Body size at young ages may influence AMH levels, but few studies have examined this. Also, no studies have examined the relation of AMH levels with breast density, a strong predictor of breast cancer risk. Methods We examined associations of early life body fatness, AMH concentrations, and breast density among 172 women in the Dietary Intervention Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Premenopausal obesity is associated with anovulatory infertility, increased androgen production and decreased serum sex hormone binding-globulin level (Pasquali and Gambineri, 2006). In addition, some studies have found lower levels of Anti-Müllerian Hormone (AMH) among obese women compared to normal weight women (Freeman et al, 2007;Steiner et al, 2010), though others report no association (Bertrand et al, 2016;Jung et al, 2017). AMH, produced by granulosa cells in the ovary, is a marker of ovarian reserve highly correlated with antral follicle count (AFC) in older premenopausal women (van Rooij, Ilse et al, 2005;La Marca and Volpe, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Premenopausal obesity is associated with anovulatory infertility, increased androgen production and decreased serum sex hormone binding-globulin level (Pasquali and Gambineri, 2006). In addition, some studies have found lower levels of Anti-Müllerian Hormone (AMH) among obese women compared to normal weight women (Freeman et al, 2007;Steiner et al, 2010), though others report no association (Bertrand et al, 2016;Jung et al, 2017). AMH, produced by granulosa cells in the ovary, is a marker of ovarian reserve highly correlated with antral follicle count (AFC) in older premenopausal women (van Rooij, Ilse et al, 2005;La Marca and Volpe, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-one studies did not meet the selection inclusion criteria: no adequate breast density data (n = 20), qualitative analysis (n = 12), editorials (n = 4), conference abstracts (n = 3), post-mortem study (n = 1), and phantom study (n = 1). Finally, 38 studies attained the inclusion criteria [1,2,3,5,11,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57] and were included in the analysis as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several MRI sequences were used to enable the precise differentiation between adipose and fibroglandular tissues; of these, non-contrast-enhanced T1-weighted was widely used either with 2D spin echo or 3D gradient echo. In fact, 16 studies (41.03%) used non-contrast-enhanced T1-weighted [1,2,26,27,28,29,31,33,35,44,45,48,49,50,51,53], while in 12 studies (30.77%) non-contrast-enhanced images were integrated with contrast-enhanced images [25,36,37,38,39,40,41,42,43,44,47,49]. In terms of breast density segmentation/measurement, the majority of the studies (20 studies; 51.28%) used FCM clustering algorithm [1,2,11,25,26,27,28,29,31,32,33,34,35,36,37,38,39,40,41,42], while 7 studies (17.95%) used FCM and N3 algorithm [45,46,47,48,49,50,51], 4 studies (10.26%) interactive thresholding algorithm [3,5,52,53], 4 studies (10.26%) in-house customized software [29,53,54,55], one study (2.56%) manual software […”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations